Fluorescent analogs of trypsin inhibitor SFTI‐1 isolated from sunflower seeds—synthesis and applications. Issue 1 (January 2014) - Lesner, Adam; Karna, Natalia; Psurski, Mateusz; Łęgowska, Anna; Wysocka, Magdalena; Guzow, Katarzyna; Sieradzan, Adam; Sieńczyk, Marcin; Trzonkowski, Piotr; Pikuła, Michał; Zieliński, Maciej; Kosikowska, Paulina; et al.
ABSTRACT This article describes the synthesis and enzymatic study of newly synthesized analogs of trypsin inhibitors SFTI‐1 that were fluorescent labeled on their N‐terminal amino groups. Two fluorescent derivatives of benzoxazole (3‐[2‐(4‐diphenylaminophenyl)benzoxazol‐5‐yl]‐l‐alanine–[(4NPh2)Ph]Box‐Ala and 3‐[2‐(2', 4', 5'‐trimethoxyphenyl)benzoxazol‐5‐yl]‐l‐alanine–[2, 4, 5‐(OMe)3Ph]Box‐Ala) were used as efficient fluorescent labels. The compounds obtained preserved their inhibitory activity and were efficient inhibitors of bovine trypsin or chymotrypsin. Nevertheless, their association inhibition constants were one or two orders of magnitude lower than those determined for unlabeled monocyclic SFTI‐1 or [Phe5]SFTI‐1, respectively. The conjugates obtained were found to be proteolytically stable in the presence of cognate enzymes. Applying such fluorescent peptides, we were able to investigate enzyme‐inhibitor complex formation using fluorescent techniques. We found that such compounds were rapidly internalized by the fibroblast or cancer cells with no cytotoxic effects. © 2013 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 102: 124–135, 2014.